The risks that COVID-19 causes to the body of pregnant and postpartum women when associated with the diagnosis of HELLP syndrome (Research, Society and Development, 2022)
The objective of this work is to discuss the relationship between HELLP Syndrome and COVID-19. The study was conducted through a bibliographic review of descriptive and qualitative approach, where articles were found in the platforms BVS, MEDLINE, LILACS and SCIELO. In the evaluation process of the pregnant woman with COVID-19 and risk for HELLP syndrome it is important to evaluate routine diagnostic tests, since the elevation of transaminase, D-dimer and platelet drop is observed, validating the suspicion of complications by HELLP syndrome. Laboratory tests for patients who have already presented clinical manifestations that may suggest HELLP Syndrome, play the role of early and differential diagnosis. The results show that pregnant women with risk factors for preeclampsia, admitted with HELLP syndrome, with endothelial damage, activation with aggregation and thrombosis, received treatment with positive evolution. It is important to emphasize the importance of a careful evaluation of the exams by the medical team and identification of signs and symptoms by the nursing team for an effective diagnosis. The results and discussion lead us to realize the difficulty in the reliable diagnosis of Hellp Syndrome and COVID-19 separately, thus hoping for more studies on the subject to differentiate signs and symptoms, which may help in the coherent diagnosis for each disease. In addition to incentives for studies on the subject, the qualification or training for the professionals of the multidisciplinary team.